An Empirical Study of Efficiency and Loan Loss Provision of Commercial Banks in China - LIU, ZIWEI (2018)
Abstract In order to study the knowledge of loan loss provision, this paper selects the panel data of 200 active commercial banks in China from 2011 to 2017. Based on the lecture review, this paper proposes four hypotheses around the loan loss provision，which include the income smoothing hypothesis, the business cycle hypothesis, the capital management assumption, and the impact of efficiency on LLP. We use STATA to establish the Stochastic Frontier Analysis (SFA) model and the Two-step Generalized Method of Moments (GMM) model to study cost efficiency and loan loss provision respectively. The empirical results show that Chinese commercial banks do have the incentive about business cycle in general. However, the results of income smoothing and capital management are not significant. As for cost efficiency, we find that the relationship between cost efficiency and loan loss reserve is positively correlated. Although this is inconsistent with the estimated results, it reflects the cautiousness of risk management of Chinese commercial banks. In addition, we confirm that the loan loss provision does have a postponement. Finally, this paper analyzes the underlying causes of the empirical results and puts forward appropriate suggestions in the policy implication section.